The therapeutic effects of low-intensity pulsed ultrasound in musculoskeletal soft tissue injuries: Focusing on the molecular mechanism - Qin, Haocheng; Du, Liang; Luo, Zhiwen; He, Zhong; Wang, Qing; Chen, Shiyi; Zhu, Yu-Lian (Frontiers in Bioengineering and Biotechnology, 2022)
Musculoskeletal soft tissue injuries are very common and usually occur during both sporting and everyday activities. The intervention of adjuvant therapies to promote tissue regeneration is of great importance to improve people’s quality of life and extend their productive life. Though many papers have focused on the positive results and effectiveness of the LIPUS on soft tissue, the molecular mechanisms standing behind the LIPUS effects are much less explored and reported, especially the intracellular signaling pathways. We incorporated all research on LIPUS in soft tissue diseases since 2005 and summarized studies that uncovered the intracellular molecular mechanism. This review will also provide the latest evidence-based research progress in this field and suggest research directions for future experiments.